Digital Parenting The Android-Based Monitoring of Children's Growth and Development for Working Mothers - Imas Mulyani; La Ode Abdul Rahman; Nur Agustini (Poltekkes Kemenkes Jakarta III, 2020)
The growth and development of children are closely related to the role of a mother, not a few mothers, and having the task of caring for children and working women, which will lead to suboptimal childcare. At this time, many android-based information system facilities that can be used to streamline child care for a mother who is a working woman. This study aimed to provide an overview and ideas of using android-based digital media in childcare to maximize children's growth and development for working mothers with a literature review method. From the study results and review of 10 selected journals, it was concluded that for parents of workers who cannot maximize childcare time or parenting time, many applications could facilitate parents to monitor the child's growth and development safely. The development of a child health nursing management information system can include healthy children, sick children, education, environment, and parenting patterns. The implication of developing a child health nursing management information system during parenting is very useful ad preventive and promotive action in children’s health. Child nurses can effectively, efficiently, quickly, and accurately identify problems that arise in the preventive process so that they are expected to make nursing interventions that are also right on target.